The Nup98 homolog APIP12 targeted by the effector AvrPiz-t is involved in rice basal resistance against Magnaporthe oryzae - Tang, Mingzhi; Ning, Yuese; Shu, Xiaoli; Dong, Bo; Zhang, Hong Yan; Wu, Dianxing; Wang, Hua; Wang, Guo-Liang; Zhou, Bo (Springer, 2017)
The effector AvrPiz-t of Magnaporthe oryzae has virulence function in rice. However, the mechanism underlying its virulence in host is not fully understood. Results In this study, we analyzed the function of AvrPiz-t interacting protein 12 (APIP12) in rice immunity. APIP12 significantly bound to AvrPiz-t and APIP6 in its middle portion and N-terminus, respectively, in yeast two-hybrid assay. Glutathione S-transferase (GST) pull-down assay further verified the interactions of APIP12 with AvrPiz-t and APIP6. APIP12 encodes a homologue of nucleoporin protein Nup98 without the conserved domain of Phe-Gly repeats and has no orthologue in other plants. Both knockout and knockdown of APIP12 caused enhanced susceptibility of rice plants to virulent isolates of M. oryzae. The expression of some pathogenesis-related (PR) genes was reduced in both knockout and knockdown mutants, suggesting that APIP12 is required for the accumulation of transcripts of PR genes upon the infection. It is worth noting that neither knockout/knockdown nor overexpression of APIP12 attenuates Piz-t resistance. Taken together, our results demonstrate that APIP12 is a virulence target of AvrPiz-t and is involved in the basal resistance against M. oryzae in rice